CollApp - collaboration chat app - Alfie Farhana Mohamed (2017)
This project’s Team Collaboration Portal is a responsive web application that provides additional features to facilitate collaboration between members of a team. These features include sub groups within main groups, polls, bookmarks, and calendar reminders. This application allows team members to organize conversations into groups, vote on suggestions and solutions quickly using the poll function, and take note of important messages and deadlines using bookmarks and reminders.